2022
DOI: 10.2147/ppa.s350917
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Acceptance and Its Associated Factors Among the Iraqi Population: A Cross Sectional Study

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic poses a serious threat to countless lives. Development of an efficient vaccination can help end the pandemic. Vaccine hesitancy/refusal is a huge issue that could stymie attempts to combat the disease. The goal of this study is to examine COVID-19 vaccine hesitancy in Iraq where at the end of July 2021, only 7.4% of the population was vaccinated. Participants and Methods: This is a cross-sectional web-based study. A survey was used to assess knowledge, attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
0
18
1
Order By: Relevance
“…Most (97%) of the studies included in our review employed a web-based recruitment method for data collection [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] . Only one study used a face-to-face data collection method, and one used both face-to-face and web-based data collection methods [87] .…”
Section: Resultsmentioning
confidence: 99%
“…Most (97%) of the studies included in our review employed a web-based recruitment method for data collection [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] . Only one study used a face-to-face data collection method, and one used both face-to-face and web-based data collection methods [87] .…”
Section: Resultsmentioning
confidence: 99%
“…In nearby Arab countries, variable levels of public acceptability of COVID-19 vaccines were noticed with higher willing in Iraq (88.6%) [ 29 ] and Egypt (88%) [ 17 ], moderate in Kuwait (67.3%) [ 30 ] and the United Arab Emirates (60.1%) [ 31 ], and it was fairly low (37.4%) in Jordan [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported contradicting findings on the association between being previously infected and the protective practices, as some studies have shown no significant association between the practices and history of infection. 23 This variation may be explained by the different sample characteristics, and/or the pandemic status when the study was conducted. Those who were in the 18–29 age group had lower practice levels than the 50 and older age group.…”
Section: Discussionmentioning
confidence: 99%
“…There are three available types of COVID-19 vaccines approved for use in Iraq: Sinopharm, 20 Pfizer 21 and AstraZeneca. 22 Although most of the Iraqi population is in favor of COVID-19 vaccination, 23 the total number of doses disbursed in Iraq at the beginning of March 2022 was 17 million doses, 24 out of a population of approximately 41 million people. The current study aims to evaluate vaccine hesitancy/refusal of the Iraqi adults towards receiving a booster dose and identify variables that may be associated with vaccine hesitancy.…”
Section: Introductionmentioning
confidence: 99%